STUDY ON GC-MS PROFILE OF FUELS PRODUCED FROM PLASTIC WASTE CONVERSION VIA THREE-CONDENSER PYROLYSIS REACTOR - Syaiful Bahri; Yuli Ambarwati; Yul Martin; Lina Marlina; Sri Waluyo (The University of Lampung, 2021)
The problem of plastic waste is very flourished in the current era of modern life. In this study, a three-condenser pyrolysis reactor was applied to obtain fuels in the form of oil#1, oil#2, and oil#3 from plastic waste. Gas Chromatography-Mass Spectroscopy (GC-MS) technique was carried out to analyze the fuel for profiling study. Characterization using GC-MS indicated the domination of hydrocarbon compounds was found oil#1. The existence of hydrocarbon compounds from oil#2 and oil#3 was displayed by chromatogram and MS database from Library Wiley 7.LIB. Meanwhile, alcohol, ether, and fatty acid were detected from oil#1 based on the chromatogram and MS database. Therefore, the samples were categorized as fuel. The result of this study corresponded to the concept of pyrolysis and be able to be implemented as an alternative energy source. Keywords: fuel, GC-MS profile, plastic waste, three-condenser pyrolysis reactor